Challenges in Selection and Utilization of Approved Secondary Kiswahili Course Books in Kenya - Ombito , Elizabeth Khalili; Omulando , Carolyne; Luganda , Massseh Musavi (African Journal of Education,Science and Technology (AJEST), 2014)
The Ministry of Education, Science and Technology in Kenya launched the multiple-choice textbook policy to be used in selection of course books and other instructional materials in public primary and secondary schools as well as colleges. This was in conformity with globalization of the textbook market which sought to enhance competition in the textbook publishing industry. The result was a list of six approved textbook titles per subject in the school curriculum that would be published in the “Orange Book” annually. Henceforth, public primary and secondary schools are required to select one textbook title per subject which then becomes the course book to be used in teaching of the respective subject. This paper examines the challenges encountered by teachers of Kiswahili in selection and utilization of the approved textbooks as course books for teaching of Kiswahili in public secondary schools in Kenya. Discussions in this paper are based on findings of research done in Webuye Division of present day Bungoma County in Kenya. The study was guided by Robert Gagne‟s Conditions of learning Theory. A survey design was used. Data was collected by interviewing eleven head teachers using a semi structured interview. A questionnaire was used to collect data from eleven teachers of Kiswahili selected randomly from eleven public secondary schools. Findings show that the multiple- choice policy guidelines were not adhered to by teachers; most teachers of Kiswahili were not conversant with policy guidelines regarding course book selection at school level; some Kiswahili textbooks were selected as course books even though they were not listed in the “Orange book”; some selected Kiswahili course books contained insufficient content in oral literature and sociolinguistics and some teachers used the course book as the sole teaching resource in Kiswahili without reference to the syllabus or any other reference book(s). The study recommended: capacity building workshops to sensitize teachers on the selection criteria and proper utilization of textbooks in classroom instruction; regular and thorough monitoring of implementation of the multiple choice school textbook policy to ensure recommended course book: learner ratios are achieved in public secondary schools in Kenya